Complete sequence and polymorphisms of female Ruditapes philippinarum (Mollusca: Bivalvia) mitochondria genome. (2nd September 2016) - Hwang, Jae Yeon; Han, Geon Goo; Park, Jung Youn; Kim, Eun-Mi; An, Cheul Min; Kang, Jung-Ha; Choi, Yun-Jaie; Kim, Eun Bae
Abstract: Mitogenome of female Ruditapes philippinarum organism was sequenced, and genomic variation and phylogeny were examined in this study. Length of the mitogenome was 22 089 bp showing 94.28% of sequence identity with previously reported sequence. Total 707 single nucleotide polymorphisms, SNPs, were detected and 50 residues were non-synonymous SNPs among the 202 SNPs in protein-coding genes. Deleted genomic fragments with of 265 bp and 322 bp were observed in non-coding regions, ND2 to ND4L and ND4L to tRNA Ile, respectively. Phylogenic analysis confirmed that used organisms were female R. philippinarum, and the species has closer evolutionary distance with genus Paphia rather than genus Meretrix . Our finding will be help to set an insight for population and evolutionary genomics of Veneroida clams as well as application to marine industry.